Automatic level control system for telephone communication channels of radio-transmitting devices - A. V. Tkacheva; A. P. Pavlov; I. E. Kashchenko (Омский научный вестник)
This article presents automatic level control system for the HF radio-transmitting devices implemented on the basis of the inexpensive of the audio codec and field-programmable gate array. The presented automatic level control system provides a quick recovery of the output level without significant surge. А compression algorithm based on the Hamming window function is used to correct the spectral mask of the signal and increase the mean-square average power of the radio-transmission path. In conclusion, the results of laboratory tests of the offered of automatic level control system.